2020
DOI: 10.3390/admsci10030039
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Growth in Innovative Technology Entrepreneurship: A Mixed-Methods Investigation

Abstract: Innovative technology enterprises are recognized internationally as an important pillar in modern economic activity. This paper presents the findings from a research combining qualitative and quantitative methods, with the specific goal of identifying and verifying the characteristics that affect their survival and growth. Results from an in-depth longitudinal qualitative case study, that examines a mature and constantly growing (in its 10-year operation) technologically innovative enterprise, reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 94 publications
1
31
0
Order By: Relevance
“…This exploratory research study focuses on understanding the concept of technology entrepreneurship through examining the lean startup approach, pivots and the factors that trigger such pivots. Technology entrepreneurship is a critical field that can enhance economic growth and create new technologydriven market opportunities [3]. Therefore, the question arises: How can a technology startup company survive in the long run?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This exploratory research study focuses on understanding the concept of technology entrepreneurship through examining the lean startup approach, pivots and the factors that trigger such pivots. Technology entrepreneurship is a critical field that can enhance economic growth and create new technologydriven market opportunities [3]. Therefore, the question arises: How can a technology startup company survive in the long run?…”
Section: Resultsmentioning
confidence: 99%
“…Entrepreneurship is considered as a positive force that contributes to the growth of both developed and developing economies. Furthermore, entrepreneurship has played a significant role in exploiting technological innovations [3]. It can be observed that researchers in the field of entrepreneurship seek to address questions such as the following: How do entrepreneurs create value propositions?…”
Section: A Technology Entrepreneurshipmentioning
confidence: 99%
See 2 more Smart Citations
“…This research combined qualitative and quantitative methods. Also, the results can help guide future theoretical and practical endeavors in innovative technology entrepreneurship (Eliakis et al 2020).…”
mentioning
confidence: 97%